The Data-to-Action Framework: A Rapid Program Improvement Process. (August 2015) - Zakocs, Ronda; Hill, Jessica A.; Brown, Pamela; Wheaton, Jocelyn; Freire, Kimberley E.
Although health education programs may benefit from quality improvement methods, scant resources exist to help practitioners apply these methods for program improvement. The purpose of this article is to describe the Data-to-Action framework, a process that guides practitioners through rapid-feedback cycles in order to generate actionable data to improve implementation of ongoing programs. The framework was designed while implementing DELTA PREP, a 3-year project aimed at building the primary prevention capacities of statewide domestic violence coalitions. The authors describe the framework's main steps and provide a case example of a rapid-feedback cycle and several examples of rapid-feedback memos produced during the project period. The authors also discuss implications for health education evaluation and practice.